Verify that -(-x)=x
![verify \: that \: - ( - x) = x \\ x = 11 \\ \: \: \: \: \: \: \: \: \: \: \: 15 verify \: that \: - ( - x) = x \\ x = 11 \\ \: \: \: \: \: \: \: \: \: \: \: 15](https://tex.z-dn.net/?f=verify+%5C%3A+that+%5C%3A++-+%28+-+x%29+%3D+x+%5C%5C+x+%3D+11+%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+++15)
Answers
Answered by
0
-(-x)=x because, -x- = +.
So,-(-x)= +x
So,-(-x)= +x
Answered by
0
Answer:
See the attachment
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/dbe/bd4b169fc50c4e3403f9a8d09646c4d5.jpg)
Similar questions